THERAPEUTIC DRUG MONITORING OF ANTICONVULSANTS IN CHILDREN IN CLINICAL PRACTICE - M. V. Leonova; M. A. Ivzhits; I. F. Tischenkova; L. L. Shteinberg (Эпилепсия и пароксизмальные состояния, 2017)
Objective. To study concentration of valproats in children with epilepsy, newborns  and infants with episyndrome  using therapeutic drug monitoring (TDM) in routine clinical practice. Materials and  methods. 75 children aged 1-18 years and 59 preterm newborns aged 0-90 days receiving valproic acid drugs were included in the study. Valproic acid concentration was measured using high performance liquid chromatography (HРLC). Results. Therapeutic concentration was achieved in 77.3%  of  children  aged  1-18  years  with  an  average  daily dose  of  25.94  mg/kg  (1021.4  mg);  overtherapeutic concentrations  were registered  in 9.3%  of the cases.  Concentration of valproic acid tended  to decrease  along with children’s age. Among children aged 1-18, a direct correlation between the daily dose (in mg/kg) and concentrations  of  valproates was observed: r=0.42 for Cmin and r=0.50 for Cmax. There was no correlation between age and concentration. In newborns,  therapeutic concentration  was achieved only in 33.9% of the cases  with an average daily dose  of 43.4 mg/kg  (82.6  mg); overtherapeutic  concentrations  were registered  in 11.9%  of the  cases.  Significant  differences  in average daily doses  and concentrations of valproic acid were found in newborns under 1 month of age; overtherapeutic concentrations  in the group of preterm newborns  under 1 month were observed  in 23.5% of the cases versus 9.5% in the group of newborns  of 2-3 months  of age (p=0.07).  Weak inverse  correlation between  age and concentration  of valproic acid was seen in newborns: r=-0.25 for Cmin and r=-0.24 for Cmax. There was no correlation between the dose and concentration of valproic acid, this explains unpredictability of the dose response  in the group of preterm newborns and low rates of achieving therapeutic concentrations.  Conclusion. Specific features of valproic acid pharmacokinetics  in newborns  and children are associated  with specific TDM parameters identified within the study; these  findings show high value of TDM.